From Epistemology to Pedagogy: Philosophical Foundations for Deep Learning in the Merdeka Curriculum - Fikri, Kamalia; Mastini; Waluyo, Joko; Mahardika, I Ketut; Soepono, Bambang (Jurnal Kiprah Pendidikan, 2025)
In Indonesia, the Independent Curriculum (Kurikulum Merdeka) was introduced as a response to challenges, but its successful implementation depends heavily on its integration with a deep learning approach. This study aims to analyze the relationship between epistemology, pedagogy, and deep learning in the Independent Curriculum through a philosophically based literature review. The analysis shows that epistemology serves as a conceptual foundation that determines perspectives on the nature of knowledge, pedagogy serves as an implementation bridge that translates philosophical foundations into learning strategies, while deep learning is the ultimate goal of conceptual understanding, critical reflection, interconceptual relationships, and the application of knowledge in real contexts. Thus, deep learning is an epistemological and pedagogical transformation that contributes to the formation of reflective, critical, and character-based students in facing the dynamics of 21st-century life.